Orthostasis Is Impaired Due to Fatiguing Intensive Acute Concentric Exercise Succeeded by Isometric Weight-Loaded Wall-Sit in Delayed-Onset Muscle Soreness: A Pilot Study - Sonkodi, Balázs; Radovits, Tamás; Csulak, Emese; Kopper, Bence; Sydó, Nóra; Merkely, Béla (Sports (Basel), 2023)
The aim of the study was to investigate any indication of diminished orthostatic tolerance as a result of fatiguing intensive acute concentric exercise with a successive isometric wall-sit followed by an orthostatic stress test, with a special focus on any distinguishable alterations due to a delayed-onset muscle soreness effect. The exercise protocol was carried out among nineteen (10 female, 9 male) junior swimmers from the Hungarian National Swim Team. All athletes showed a positive orthostatic stress test right after our exercise protocol. The diastolic blood pressure was significantly lower due to the delayed-onset muscle soreness effect in the standing position after the supine position of the orthostatic stress test, in contrast to the athletes who did not experience delayed-onset muscle soreness. Furthermore, the heart rate was dysregulated in athletes with a delayed-onset muscle soreness effect when they assumed a supine position after the sustained standing position during the orthostatic stress test, in contrast to the athletes without delayed-onset muscle soreness. Interesting to note is that, in three subjects, the sustained standing position decreased the heart rate below the level of the initial supine position and six athletes experienced dizziness in the standing position, and all of these athletes were from the group that experienced delayed-onset muscle soreness. Accordingly, this study, for the first time, demonstrated that delayed-onset muscle soreness impairs orthostasis after unaccustomed fatiguing intensive acute concentric exercise with a successive isometric weight-loaded wall-sit; however, validation of this association should be investigated in a larger sample size.